Technical Report: Influence of an enhanced use of biomass for energy on the CO2 concentration in the atmosphere. (4th August 2014) - Ahamer, Gilbert
In this study, the influence of different strategies of 'biomass for energy' was modelled by means of a global carbon cycle model in order to compute the annual atmospheric CO2 concentration until the year 2100. A 'Combined Energy and Biosphere Model' was developed on the basis of the Osnabrück Biosphere Model (OBM).